2014
DOI: 10.4103/0019-5154.135475
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus deoxyribonucleic acid may not be detected in non-genital benign papillomatous skin lesions by polymerase chain reaction

Abstract: Background:Papillomatosis is a known histopathologic pattern usually seen in human papillomavirus (HPV) infection and verruca vulgaris is the typical example. This pattern is also detected in some other benign cutaneous lesions such as nevus sebaceous (NS), seborrheic keratosis (SK), trichilemmoma (TL) and inverted follicular keratosis (IFK). The association between papillomatous lesions and HPV infection is questionable.Objective:The objective of this study was to investigate the presence of HPV deoxyribonucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…They are considered a sign of aging skin in general and extrinsic aging, particularly due to chronic ultraviolet (UV) exposure. In contrast, a viral hypothesis suggesting the involvement of HPV has not been substantiated by recent studies 19, 20 . Nevertheless, HPV p16 expression has been found in genital SKs at a frequency of between 65% and 69.6% 21, 22 .…”
Section: Pathogenesismentioning
confidence: 86%
“…They are considered a sign of aging skin in general and extrinsic aging, particularly due to chronic ultraviolet (UV) exposure. In contrast, a viral hypothesis suggesting the involvement of HPV has not been substantiated by recent studies 19, 20 . Nevertheless, HPV p16 expression has been found in genital SKs at a frequency of between 65% and 69.6% 21, 22 .…”
Section: Pathogenesismentioning
confidence: 86%
“…and Kambiz et al. could not find a positive association between HP viruses and the development of SK 43,44 …”
Section: Pathogenesismentioning
confidence: 84%
“…[ 1 2 3 5 6 9 ] IFK has histologic similarities to irritated seborrheic keratosis, keratoacanthoma, trichilemmoma, and verruca vulgaris, but most studies have found IFK to be consistently negative for HPV by immunohistochemistry, in situ hybridization and polymerase chain reaction. [ 1 2 3 10 11 12 13 14 ]…”
Section: Discussionmentioning
confidence: 99%